Evaluation of Safe Insertion Angles for Spinal Needles and Safe Intensity of the Holmium:YAG Laser during Percutaneous Laser Disc Ablations in Feline Cadavers - Zhenglin Piao; Young-ung Kim; Jongchan Ko; Jumjae Lee; Daeyoung Choi; Namsoo Kim (Veterinary Sciences, 2024)
In the context of veterinary medicine, minimally invasive techniques for feline spinal surgery remain underexplored, particularly for percutaneous laser disc ablation (PLDA) when using the Holmium:YAG (Ho:YAG) laser. This study aimed to refine the application of the Ho:YAG laser in PLDA by determining the optimal laser intensity and safe insertion angles for the thoracic and lumbar intervertebral discs (IVDs) in cats. Through utilizing computed tomography (CT) for precise guidance, this research involved a cadaveric study of 10 cats to evaluate the spatial configurations that allow for safe needle insertions and effective laser ablation. Various energy settings of the Ho:YAG laser (20 J, 40 J, and 60 J) were tested to ascertain the balance between adequate disc vaporization and minimal adjacent tissue damage. The results demonstrate that a 40 J setting is the most effective in achieving significant disc decompression without compromising surrounding tissue integrity. Additionally, the CT scans proved crucial in confirming the accuracy of the needle placement and the safety of the laser application angles. This study established that the 40 J setting on the Ho:YAG laser, combined with CT-guided insertion techniques, offers a reliable method for PLDA, thus enhancing the safety and efficacy of feline spinal surgeries.